2016
DOI: 10.1128/jcm.01038-16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Hologic Panther Transcription-Mediated Amplification Assay for Detection of Mycoplasma genitalium

Abstract: fThe detection of Mycoplasma genitalium was evaluated on 1,080 urine samples by the use of a Panther instrument. Overall sensitivity, specificity, positive predictive values, and negative predictive values were 100%, 99.4%, 93.6%, and 100%, respectively. Detection of M. genitalium by the use of the Panther transcription-mediated amplification assay offers a simple, accurate, and sensitive platform for diagnostic laboratories. Mycoplasma genitalium is a common cause of nongonococcal urethritis (NGU) in men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
(26 reference statements)
1
20
0
Order By: Relevance
“…Previous studies in Sydney and Melbourne, of 508 and 515 men, respectively, both failed to detect pharyngeal Mgen using PCR. TMA has a higher analytical sensitivity than PCR for Mgen,27 although the Aptima Mycoplasma genitalium Assay (Hologic) has yet to be validated for detection of pharyngeal Mgen. Given the organism load of Mgen is up to 100 times lower than that of CT,28 and may be at particularly low loads in the pharynx, TMA may be more likely to detect pharyngeal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Sydney and Melbourne, of 508 and 515 men, respectively, both failed to detect pharyngeal Mgen using PCR. TMA has a higher analytical sensitivity than PCR for Mgen,27 although the Aptima Mycoplasma genitalium Assay (Hologic) has yet to be validated for detection of pharyngeal Mgen. Given the organism load of Mgen is up to 100 times lower than that of CT,28 and may be at particularly low loads in the pharynx, TMA may be more likely to detect pharyngeal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Several companies have commercialized CE-marked multiplex PCR assays for the detection of sexually transmitted pathogens, including M. genitalium ( 6 , 7 , 9 , 10 ). As an alternative to PCR, Hologic, Inc. developed a research-use-only (RUO) TMA assay for the detection of M. genitalium ( 8 , 11 , 12 ) and recently commercialized the Aptima Mycoplasma genitalium TMA (MG-TMA) assay CE-marked for in vitro diagnosis (CE-IVD), which is available on the Panther platform. Commercial tests that have been CE-marked for document conformity usually suffer from limited clinical validation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we validated the performance characteristics of four TMA NAAT assays for the detection of ribosomal RNAs from M. genitalium. We found that these assays are sensitive and specific for the detection of multiple stains of M. genitalium and have Similarly to NAATs designed to detect other sexually transmitted infections such as Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis, the detection of rRNA of M. genitalium affords a particularly sensitive method for detecting the organism in vivo, leading to improved clinical diagnosis of M. genitalium infection compared to that with NAATs that target genomic DNA of the organism (20)(21)(22). This difference in relative test clinical sensitivity may be due to the disparity between genomic DNA and rRNA content in the cell (i.e., a single DNA genome versus an estimated hundreds to thousands of rRNA copies per cell) (29), enabling the detection of low titers of M. genitalium in patient specimens (30,31).…”
Section: Discussionmentioning
confidence: 97%
“…This is the first study to use only rRNA-specific NAATs for the components of a composite comparator reference standard for the evaluation of an rRNA-based molecular test for M. genitalium detection. Previous studies investigating the clinical perfor- mance of rRNA-based NAAT assays for M. genitalium used a reference standard consisting of a combination of tests that detected rRNA and genomic DNA of M. genitalium (20,21). This mixed reference standard approach has the potential to introduce bias into the analyses, since the lower sensitivity of DNA-based tests can decrease the rate of DNA-positive/RNA-positive consensus results obtained in the analysis, potentially resulting in artificially lowered specificity estimates for the RNA-based diagnostic test under evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation